Pelatihan Pemasaran Digital Pada UMKM Di Desa Segaran Kecamatan Delanggu Kabupaten Klaten Jawa Tengah - Poppy Septinawati; Tasya Oktavia Ekawati; Yoga Surya Kusuma; Dian Vika Laurenshia; Agni Astungkara (Jurnal Ekonomi, Bisnis dan Manajemen, 2023)
Marketing activities have experienced a fairly rapid development along with development of information technology. In today's all-digital era, digital marketing formed a new strategy that is very important in the marketing of a company, especially for businesses such as online stores that allow buying and selling at once. Current company competing in developing their marketing strategies in achieving and retain customers. The virtual world is getting closer to everyday life we, making the era of digitalization we cannot avoid. The customer is currently in commit Interaction with the company is carried out by utilizing social media and applications growing rapidly. This can be caused by various factors that go wrong only environmental factor. So the author makes an activity that can help these problems by holding socialization of the Role of Digital Marketing for MSMEs in this era digitization. The method of implementing community service activities is by doing an approach in the form of socialization and useful training to add insight/education to the community so that the knowledge gained can be applied in activities MSMEs. There are three stages of implementation, namely the planning stage in the stage planning, students collect data first through surveys and interviews regarding MSMEs in Segaran Village along with the behavior of MSMEs in the Village the. Every student who takes part in the community service activity program show the attitude of responsibility as an executor, it is shown by every student on time while carrying out each task. Good communication has been shown every students during discussions and evaluations after community activities. Student always conduct an evaluation to improve an activity that has been carried out to achieve more optimal activities. In the era of digital technology has changed the human way of life communicate, act, and make decisions. Marketing activities were not separated from influence of digital technology. The term digital-based marketing has evolved from Initially marketing activities for goods and services using digital channels to broader understanding, namely the process of acquiring consumers, building preferences consumers, promote brands, maintain consumers, and increase sales.